2020
DOI: 10.1002/mp.14183
|View full text |Cite
|
Sign up to set email alerts
|

Stage detection of mild cognitive impairment via fMRI using Hilbert Huang transform based classification framework

Abstract: This work aims to establish a classification framework for the diagnosis of mild cognitive impairment (MCI) at different stages (early MCI and late MCI) through direct analysis of restingstate functional magnetic resonance imaging (rs-fMRI) signals and using the accuracy (total correct rate), specificity (correct rate of late MCI) and sensitivity (correct rate of early MCI) to validate its classification performance. Methods: All fMR images of subjects were parcellated into 116 regions of interest (ROIs) by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Contrastingly, the fALFF in the left MFG in the MCI-lowEF group is lower compared to HC, while fALFF of the cerebellar vermis is higher than HC. The majority of regions have been reported in prior MCI or AD studies (Cai et al, 2018;Long et al, 2018;Shi and Liu, 2020;Wang et al, 2021c). Compared to HC, the two groups all demonstrated significant fALFF differences in the left MFG.…”
Section: Discussionmentioning
confidence: 79%
“…Contrastingly, the fALFF in the left MFG in the MCI-lowEF group is lower compared to HC, while fALFF of the cerebellar vermis is higher than HC. The majority of regions have been reported in prior MCI or AD studies (Cai et al, 2018;Long et al, 2018;Shi and Liu, 2020;Wang et al, 2021c). Compared to HC, the two groups all demonstrated significant fALFF differences in the left MFG.…”
Section: Discussionmentioning
confidence: 79%
“…The procedure was repeated until every enrolled subject was used as the test set. Then, we calculated the classification accuracy (Shi and Liu, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al also used multiple brain network features and conducted feature selection by three different algorithms 8 . Shi and Liu extracted features by calculating the Hilbert weighted frequencies (HWFs) from decomposed rs-fMRI signals, with independent two-sample t -test as feature selection method for SVM 25 . Collectively, these results suggest the optimal feature selection from multi-modal MRI data might be critical to improve classification performance.…”
Section: Discussionmentioning
confidence: 99%
“…Nozadi et al also used PET images for classification, comparing FDG and Amyloid ( AV-45) PET biomarkers 24 . Shi and Liu extracted features from rs-fMRI signals 25 , and Sheng et al processed thousands of brain network features by graph theory for classification 26 . Wee et al have indicated the multi-modal neuroimaging approach with structural and functional connectivity analyses significantly improves the identification accuracy of MCI 27 .…”
Section: Introductionmentioning
confidence: 99%